Phase II study of cabozantinib in patients with progressive glioblastoma: subset analysis of patients with prior antiangiogenic therapy. Issue 2 (3rd October 2017) - Cloughesy, Timothy F; Drappatz, Jan; de Groot, John; Prados, Michael D; Reardon, David A; Schiff, David; Chamberlain, Marc; Mikkelsen, Tom; Desjardins, Annick; Ping, Jerry; Holland, Jaymes; Weitzman, Ron; et al.
Abstract: Background: Cabozantinib is a potent, multitarget inhibitor of MET and vascular endothelial growth factor receptor 2 (VEGFR2). This open-label, phase II trial evaluated cabozantinib in patients with recurrent or progressive glioblastoma (GBM). Methods: Patients were initially enrolled to a starting cabozantinib dose of 140 mg/day, but the starting dose was amended to 100 mg/day because of safety concerns. Treatment continued until disease progression or unacceptable toxicity. The primary endpoint was objective response rate, assessed by an independent radiology facility using modified Response Assessment in Neuro-Oncology criteria. Additional endpoints included duration of response, 6-month and median progression-free survival, overall survival, glucocorticoid use, and safety. Results: Among 222 patients enrolled, 70 had received prior antiangiogenic therapy. Herein, we report results in this subset of 70 patients. The objective response rate was 4.3%, and the median duration of response was 4.2 months. The proportion of patients alive and progression free at 6 months was 8.5%. Median progression-free survival was 2.3 months, and median overall survival was 4.6 months. The most common adverse events reported in all patients, regardless of dose group, included fatigue (74.3%), diarrhea (47.1%), increased alanine aminotransferase (37.1%), headache (35.7%), hypertension (35.7%), and nausea (35.7%); overall, 34 (48.6%) patients experienced adverse events that resulted in dose reductions. Conclusions: Cabozantinib treatment appeared to have modest clinical activity with a 4.3% response rate in patients who had received prior antiangiogenic therapy for GBM. Clinical Trials Registration Number: NCT00704288 (https://www.clinicaltrials.gov/ct2/show/NCT00704288 )